2021
DOI: 10.3390/cancers13133215
|View full text |Cite
|
Sign up to set email alerts
|

Significant Decrease in Annual Cancer Diagnoses in Spain during the COVID-19 Pandemic: A Real-Data Study

Abstract: The COVID-19 pandemic has caused a profound change in health organizations at both the primary and hospital care levels. This cross-sectional study aims to investigate the impact of the COVID-19 pandemic in the annual rate of new cancer diagnosis in two university-affiliated hospitals. This study includes all the patients with a pathological diagnosis of cancer attended in two hospitals in Málaga (Spain) during the first year of pandemic. This study population was compared with the patients diagnosed during th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
32
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(43 citation statements)
references
References 24 publications
5
32
0
4
Order By: Relevance
“…In the case of the tertiary referral hospital in Girona, which is a reference center for oncology in the province, a reduction in cancer diagnoses of around 6% was detected at the end of 2020, and in Figueres Hospital, which is a county center, there was a 20% reduction in cancer diagnoses from 2019 to 2020 overall. To the best of our knowledge, the only study to have analyzed cancer data based on pathology results in Spain observed a 17% reduction in diagnoses, this finding being similar to those of other studies [ 15 , 16 ]. These figures reflect the effort to recover care services, especially oncology referrals, despite their saturation after reaching a 70% reduction in activity during the first wave, as other studies have shown [ 17 , 18 , 19 ].…”
Section: Discussionsupporting
confidence: 88%
“…In the case of the tertiary referral hospital in Girona, which is a reference center for oncology in the province, a reduction in cancer diagnoses of around 6% was detected at the end of 2020, and in Figueres Hospital, which is a county center, there was a 20% reduction in cancer diagnoses from 2019 to 2020 overall. To the best of our knowledge, the only study to have analyzed cancer data based on pathology results in Spain observed a 17% reduction in diagnoses, this finding being similar to those of other studies [ 15 , 16 ]. These figures reflect the effort to recover care services, especially oncology referrals, despite their saturation after reaching a 70% reduction in activity during the first wave, as other studies have shown [ 17 , 18 , 19 ].…”
Section: Discussionsupporting
confidence: 88%
“…In the past months, a substantial body of literature has investigated the effects of the COVID-19 crisis on cancer diagnosis (Andrew et al 2021 ; De Luca et al 2021 ; Erdmann et al 2021 ; Gurney et al 2021 ; Jacob et al 2021 ; Kuzuu et al 2021 ; Patt et al 2020 ; Peacock et al 2021 ; Piontek et al 2021 ; Reichardt et al 2021 ; Ruiz-Medina et al 2021 ; Stang et al 2020 ; Tsibulak et al 2020 ; Vardhanabhuti and Ng 2021 ; Voigtländer et al 2021 ). For example, a study, using national data from New Zealand, showed that cancer registrations (new diagnoses of primary malignant cancers) declined by 40% in this country in March–April 2020 compared with 2018–2019, and that registrations increased in the subsequent months to reach pre-lockdown levels (Gurney et al 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…This decrease in cancer registrations was associated with a decline in endoscopies and radiation therapy attendances. In another study conducted at two hospitals in Spain, there was a 17% decrease in cancer diagnoses in 2020 compared with 2019, and the most impacted cancers were central nervous system, kidney and prostate neoplasms (Ruiz-Medina et al 2021 ). These findings were corroborated in a third study from Belgium, as there was a 44% reduction in the diagnoses of invasive cancers in this country in April 2020 compared with April 2019 (Peacock et al 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although not directly evaluating a change in stages at presentation, Peacock et al noted a 56% decline in breast cancer diagnoses in Belgium during the pandemic [ 14 ]. Scioscia et al estimated the number of missed breast cancer diagnoses in Italy due to the interruption in screening programs at 2793 [ 15 ], and in Spain, breast cancer diagnoses showed a 26.1% decrease in 2020 [ 16 ]. These numbers show the profound impact of the pandemic on oncological services and help to identify patients at risk.…”
Section: Discussionmentioning
confidence: 99%